Impact of Perceived Empathic Self-Efficacy on Perceived Social Self-Efficacy: a Cross-Sectional Study Among Prospective Health Workers - Arslan , Aysel; Atak , İfakat (Insight: the psychological dimensions of society, 2025)
In order to be successful in business life, emotional characteristics are also needed in addition to the specific physical characteristics required from employees. The empathic and social self-efficacy levels of healthcare professionals are important for job success in healthcare organizations. A highly empathic and social self-efficacy healthcare professional will deliver effective service by establishing good communication and approaching the patient by understanding their conditions. Similarly, since the emotional awareness of a healthcare professional with a high level of empathic and social self-efficacy will be high, coordination with colleagues will be easy. This study aims to measure the empathic and social self-efficacy perceptions that reveal the humanistic skills of students receiving education in the healthcare field and to create a resource by revealing the relationship between them. In this way, delivering health services, which is a team effort, will be easier and more harmonious, and the service’s success will increase. Methods. For the current study, a survey was applied to 374 healthcare professional candidates. The research objective was achieved by utilizing the “Perceived Empathic Self-efficacy and Social Self-efficacy Scale” as the primary assessment instrument. The data obtained in the study were analyzed using SPSS and LISREL programs. Results. Based on the findings, a positive and moderate relationship (r=0.58) was observed between perceived empathic and social self-efficacy. It is seen that empathic self-efficacy and social self-efficacy perceived by health worker candidates do not differ according to gender, class, and age variables. Discussion and Conclusions. Perceived empathic self-efficacy positively affects perceived social self-efficacy. It is seen that perceived empathic self-efficacy explains approximately 34% of the change in perceived social self-efficacy. Future research should expand on the relationship between empathy and social self-efficacy by including diverse professional groups and additional variables, such as emotion blindness or emotional intelligence. This will provide a deeper understanding of how these factors contribute to professional success.
Keywords: Array; Array; Array; Array; Array; Array